Introducing global peat-specific temperature and pH calibrations based on brGDGT bacterial lipids. (1st July 2017) - Naafs, B.D.A.; Inglis, G.N.; Zheng, Y.; Amesbury, M.J.; Biester, H.; Bindler, R.; Blewett, J.; Burrows, M.A.; del Castillo Torres, D.; Chambers, F.M.; Cohen, A.D.; Evershed, R.P.; et al.
Highlights: Analysis of brGDGT distributions in global peat dataset. Correlation of brGDGT distributions with peat pH and mean annual air temperature. Development of peat-specific temperature and pH proxies. Abstract: Glycerol dialkyl glycerol tetraethers (GDGTs) are membrane-spanning lipids from Bacteria and Archaea that are ubiquitous in a range of natural archives and especially abundant in peat. Previous work demonstrated that the distribution of bacterial branched GDGTs (brGDGTs) in mineral soils is correlated to environmental factors such as mean annual air temperature (MAAT) and soil pH. However, the influence of these parameters on brGDGT distributions in peat is largely unknown. Here we investigate the distribution of brGDGTs in 470 samples from 96 peatlands around the world with a broad mean annual air temperature (−8 to 27 °C) and pH (3–8) range and present the first peat-specific brGDGT-based temperature and pH calibrations. Our results demonstrate that the degree of cyclisation of brGDGTs in peat is positively correlated with pH, pH = 2.49 × CBTpeat  + 8.07 ( n  = 51, R 2  = 0.58, RMSE = 0.8) and the degree of methylation of brGDGTs is positively correlated with MAAT, MAATpeat (°C) = 52.18 × MBT5me ′ − 23.05 ( n  = 96, R 2  = 0.76, RMSE = 4.7 °C). These peat-specific calibrations are distinct from the available mineral soil calibrations. In light of the error in the temperature calibration (∼4.7 °C), we urge caution in any application to reconstruct late Holocene climate variability, where the climatic signals are relatively small, and the duration of excursions could be brief. Instead, these proxies are well-suited to reconstruct large amplitude, longer-term shifts in climate such as deglacial transitions. Indeed, when applied to a peat deposit spanning the late glacial period (∼15.2 kyr), we demonstrate that MAATpeat yields absolute temperatures and relative temperature changes that are consistent with those from other proxies. In addition, the application of MAATpeat to fossil peat (i.e. lignites) has the potential to reconstruct terrestrial climate during the Cenozoic. We conclude that there is clear potential to use brGDGTs in peats and lignites to reconstruct past terrestrial climate.